HPLC method validation for modernization of the tetracycline hydrochloride capsule USP monograph - Emad M. Hussien (Faculty of Pharmacy, Cairo University, 2014)
This paper is a continuation to our previous work aiming at development and validation of a reversed-phase HPLC for modernization of tetracycline-related USP monographs and the USP general chapter <226>. Previous results showed that the method is accurate and precise for the assay of tetracycline hydrochloride and the limit of 4-epianhydrotetracycline impurity in the drug substance and oral suspension monographs. The aim of the current paper is to examine the feasibility of the method for modernization of USP tetracycline hydrochloride capsule monograph. Specificity, linearity, accuracy and precision were examined for tetracycline hydrochloride assay and 4-epianhydrotetracycline limit. The method was linear in the concentration range from 80% to 160% (r>0.9998) of the assay concentration (0.1 mg/mL) for tetracycline hydrochloride and from 50% to 150% (r>0.997) of the acceptance criteria specified in tetracycline hydrochloride capsule monograph for 4-epianhydrotetracycline (NMT 3.0%). The recovery at three concentration levels for tetracycline hydrochloride assay was between 99% and 101% and the RSD from six preparations at the concentration 0.1 mg/mL is less than 0.6%. The recovery for 4-epianhydrotetracycline limit procedure over the concentration range from 50% to 150% is between 96% and 102% with RSD less than 5%. The results met the specified acceptance criteria.